(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
The synthesis of thiocol oligomers based on local raw materials and their modification with unsaturated compounds belongs to the field of chemistry and materials science, and includes the processing of thiocol oligomers, raw materials and their modification with unsaturated compounds. These processes are an important way to produce environmentally friendly and economically efficient materials